Exploring how soccer players with perfectionism navigate challenges in talent pathways - Donachie, T.; Mallinson-Howard, S.; Hill, A.; Tamminen, K. (BASES Conference 2024, 2024)
Talent pathways are essential for the development and success of aspiring footballers, yet limited research exists on their experiences within these pathways. The study pro vides the first qualitative exploration of the experiences associated with perfectionism among footballers in talent pathways and how they respond to challenges in this con text. A two-stage approach was adopted. Following institu tional ethical approval, in stage one, footballers completed self-report measures of perfectionism and perfectionistic cognitions. From a sample of 26 footballers from talent pathways (e.g., national team pathway, performance schools, club-based academies) who self-identified as per fectionists, 22 footballers (10 males, 12 females, Mage = 16.31 years, SD = 3.73) met the criteria and agreed to participate. In stage two, footballers with higher levels of perfectionism and perfectionistic cognitions (1 SD above the mean of samples from previous studies) participated in semi-structured one-to-one interviews. Four participated in pilot interviews (Mage = 17 years, SD = 5.35) and the remaining 18 formed the final sample for interviews (10 female, 8 male; 14 adolescents, 4 adults, Mage = 16.17 years, SD = 3.47). The main interview questions were based on previous qualitative studies of perfectionism in sport (e.g., Hill et al., 2015) and aimed to explore experi ences related to Flett and Hewitt`s (2016) concept of per fectionistic reactivity (e.g., "Can you describe in what way(s) your perfectionism shows itself?"). The analysis followed the steps of semantic thematic analysis as outlined by Braun and Clarke (2021), and to ensure qualitative quality, Tracy`s (2010) "big eight" criteria were rigorously followed. Seven themes were identified: (1) cycles of anxiety, (2) sadness at being a substitute, (3) self-criticism and hopelessness during slumps, (4) ruminating on mistakes, (5) worthless when injured, (6) shame in success and intolerance of defeat, and (7) punishment for failure: psychological distress. Participants experienced heightened anxiety before and during performance, especially when they were substitutes. In the face of poor performance, mistakes, and injuries, participants were likely to respond with self-criticism, hope lessness, and negative emotions. Post-match, they rumi nated after both success and defeat, with some reporting extreme psychological difficulties (e.g., eating disorder symptoms). The results suggest that perfectionism impacts aspiring footballers, often hindering routine parts of parti cipation and ability to handle setbacks and performance difficulties. This study highlights the need for targeted sport psychology interventions to address perfectionistic tendencies and support athlete well-being.